2021
DOI: 10.3390/ijms222413225
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the Molecular Pathway in Myotonic Dystrophy

Abstract: Myotonic dystrophy is the most common muscular dystrophy in adults. It consists of two forms: type 1 (DM1) and type 2 (DM2). DM1 is associated with a trinucleotide repeat expansion mutation, which is transcribed but not translated into protein. The mutant RNA remains in the nucleus, which leads to a series of downstream abnormalities. DM1 is widely considered to be an RNA-based disorder. Thus, we consider three areas of the RNA pathway that may offer targeting opportunities to disrupt the production, stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…It has been suggested that the increased stability of the mutant CUG-containing mRNA might be due to binding of MBNL1 to the mutant CUG repeats. Therefore, many studies have been focused on the identification of small molecules and other approaches that might disrupt binding of MBNL1 to the mutant CUG repeats and might reduce the number of CUG foci, improving splicing of mRNAs, regulated by MBNL1 (reviewed in references [ 59 , 60 , 61 , 62 , 63 ]). These small molecules have been identified using the screening of the compound libraries or synthesized by special design.…”
Section: Therapeutic Targets In Dm1 and Dm2mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the increased stability of the mutant CUG-containing mRNA might be due to binding of MBNL1 to the mutant CUG repeats. Therefore, many studies have been focused on the identification of small molecules and other approaches that might disrupt binding of MBNL1 to the mutant CUG repeats and might reduce the number of CUG foci, improving splicing of mRNAs, regulated by MBNL1 (reviewed in references [ 59 , 60 , 61 , 62 , 63 ]). These small molecules have been identified using the screening of the compound libraries or synthesized by special design.…”
Section: Therapeutic Targets In Dm1 and Dm2mentioning
confidence: 99%
“…Main criteria to evaluate the efficacy of the identified small molecules included prevention of MBNL1 binding to the expanded CUG repeats, reduction in CUG foci and correction of splicing targets, known to be misregulated in DM1 using cell culture lines from patients with DM1 or DM1 mice. Using these parameters, various small molecules correcting MBNL1 activity and improving splicing were identified and their number is growing fast [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. The list of small molecules that improve MBNL1 activity includes anti-infective agents (such as pentamidine, furamidine and erythromycin) [ 64 , 65 , 66 ], compounds affecting microtubules [ 68 ] and small molecules increasing MBNL1 levels (such as the anti-autophagic drugs and inhibitors of HDAC) [ 67 , 71 ].…”
Section: Therapeutic Targets In Dm1 and Dm2mentioning
confidence: 99%
See 1 more Smart Citation
“… Therapeutic approaches for DM1 discussed in the reviews in the Special Issues of the journal. They include the CRISPR/Cas approach [ 5 , 6 ], as well as the application of small molecules, restoring MBNL1 and CUGBP1 activities or correcting splicing via other RNA-binding proteins [ 7 , 8 , 9 , 10 ]. Although indirectly, several review papers referred to the use of AONs as a potential therapy for DM1 [ 5 , 7 , 8 , 10 , 11 , 12 ].…”
Section: Figurementioning
confidence: 99%
“…Two reviews by Dr. Berglund’s and Dr. Brook’s groups focused on identified or synthesized small molecules correcting MBNL1 and CUGBP1 [ 7 , 10 ]. Among the small molecules, which could be used as potential therapeutics, are kinase inhibitors [ 10 ]. The Special Issue also shows that microRNAs could be used to normalize MBNL1 and CUGBP1 in DM1 [ 11 ].…”
mentioning
confidence: 99%